PENERAPAN PEMBELAJARAN MATEMATIKA REALISTIK TERHADAP KEMAMPUAN BERPIKIR KREATIF DAN LOGIS SISWA MTs - Muhammad Yusup Kurniansyah; Ahmad Rosandi; Luvy Sylviana Zanthy (Departement of Mathematics Education, 2019)
This study aimed to analyze and study about applying realistic mathematic approach to Mathematical creative thinking ability and Mathematical logical thinking ability MTs students. the method used in this study is the method of paired samples with quantitative data. The population in this study were students of MTs in West Bandung regency with a sample of 25 people who set out with purposive sampling technique in one of the private MTs in West Bandung regency. Instruments in this study a mathematical creative thinking ability tests by 4 items and test mathematical ability to think logically as one item. Then the results of this study came to the conclusion that, the relationship between these two variables showed a positive direction and the average mathematical ability to think creatively is not lower than the average of mathematical logical thinking ability if applied by realistic mathematic approach.